Kathoey Sub-culture and Ronggeng Dance at the Orak Lawoi Pelacak Festival in Southwest Thailand - Premalatha Thiagarajan (Wacana Seni Journal of Arts Discourse, 2019)
This article focuses on the Orak Lawoi (semi nomadic sea people) in Phuket and Ko Sireh islands and their biannual ritual celebration called Pelacak, celebrated for three days during the full moons in May and October. During this celebration, sea-gypsy communities in Sapam, Rawai and Ko Sireh perform ceremonial ritual through an elaborately decorated model boat that is launched into the sea with ritual items to accompany the recently departed spirits out to the sea. This festival encompasses songs, music and dance performed at the periphery of the ritual space as well as during the procession of the model boat. During this celebration, I witnessed the presence of kathoeys (an identifier for transgendered women, effeminate men and transsexuals in Thailand) in different circumstances as spectators, as backstage disco dancers and visible ronggeng or rong ngeng (a social dance or folk-dance form), performers. I discuss the visibility of kathoeys and the ways in which they negotiate their identity in different spaces. I suggest that within the Orak Lawoi mainstream group, kathoeys emerge as a sub-culture gender/sexual group, whose participation in these spaces is unavoidable but ambivalent, depending on the level of tolerance of the community towards the non-normative gender/sexual groups.